2016
DOI: 10.3390/nu8120772
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selenium Supplementation on Glucose Homeostasis and the Expression of Genes Related to Glucose Metabolism

Abstract: The aim of the study was to evaluate the effect of selenium supplementation on the expression of genes associated with glucose metabolism in humans, in order to explain the unclear relationship between selenium and the risk of diabetes. For gene expression analysis we used archival samples of cDNA from 76 non-diabetic subjects supplemented with selenium in the previous study. The supplementation period was six weeks and the daily dose of selenium was 200 µg (as selenium yeast). Blood for mRNA isolation was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…In another study elsewhere, Wang et al (2014) demonstrated that high doses of selenium (200 mg/kg) exacerbated hyperglycemia by promoting the expression of carboxykinase phosphoenolpyruvate and glucose 6-phosphatase enzymes involved in gluconeogenesis. The study by Jablonska et al (2016) demonstrated that low doses of selenium improve homeostasis of glucose and the expression of genes related to glucose metabolism at different levels of regulation, linked to insulin signaling, glycolysis, and pyruvate metabolism. NFBG levels are a vital parameter in comprehending the severity of type 2 diabetes (Group 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In another study elsewhere, Wang et al (2014) demonstrated that high doses of selenium (200 mg/kg) exacerbated hyperglycemia by promoting the expression of carboxykinase phosphoenolpyruvate and glucose 6-phosphatase enzymes involved in gluconeogenesis. The study by Jablonska et al (2016) demonstrated that low doses of selenium improve homeostasis of glucose and the expression of genes related to glucose metabolism at different levels of regulation, linked to insulin signaling, glycolysis, and pyruvate metabolism. NFBG levels are a vital parameter in comprehending the severity of type 2 diabetes (Group 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study in Poland which was conducted in 2013 showed that Se supplements improved HBA1C levels but not fasting glucose levels [20]. However, a study conducted in Taiwan examined elderly individuals and found out that higher Se levels had a correlation with higher fasting glucose levels and with higher blood total cholesterol and triglyceride levels [21].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, dietary selenium can increase total triglyceride, total cholesterol and nonesterified fatty acids in the liver and adipose tissues and the high-selenium diet can also alter protein metabolism and elevate total protein concentrations in both liver and muscle of pigs [75]. Selenium can affect glycemic control through insulin signaling, glycolytic pathway and pyruvate metabolism in humans [76]. In aquatic animals, dietary selenium can effectively improve flesh quality of rainbow trout (Oncorhynchus mykiss) through inhibition of protein degradation [77].…”
Section: Accepted Manuscriptmentioning
confidence: 98%